Induction of apoptosis in human breast cancer cells via caspase pathway by vernodalin isolated from centratherum anthelminticum (L.) seeds - Looi, C.Y.; Arya, A.; Cheah, F.K.; Muharram, B.; Leong, K.H.; Mohamad, K.; Wong, W.F.; Rai, N.; Mustafa, Mohd Rais (Public Library of Science, 2013)
Background: Centratherum anthelminticum (L.) seeds (CA) is a well known medicinal herb in Indian sub-continent. We recently reported anti-oxidant property of chloroform fraction of Centratherum anthelminticum (L.) seeds (CACF) by inhibiting tumor necrosis factor-Î± (TNF-Î±)-induced growth of human breast cancer cells. However, the active compounds in CACF have not been investigated previously. Methodology/Principal Findings: In this study, we showed that CACF inhibited growth of MCF-7 human breast cancer cells. CACF induced apoptosis in MCF-7 cells as marked by cell size shrinkage, deformed cytoskeletal structure and DNA fragmentation. To identify the cytotoxic compound, CACF was subjected to bioassay-guided fractionation which yielded 6 fractions. CACF fraction A and B (CACF-A, -B) demonstrated highest activity among all the fractions. Further HPLC isolation, NMR and LC-MS analysis of CACF-A led to identification of vernodalin as the cytotoxic agent in CACF-A, and -B. 12,13-dihydroxyoleic acid, another major compound in CACF-C fraction was isolated for the first time from Centratherum anthelminticum (L.) seeds but showed no cytotoxic effect against MCF-7 cells. Vernodalin inhibited cell growth of human breast cancer cells MCF-7 and MDA-MB-231 by induction of cell cycle arrest and apoptosis. Increased of reactive oxygen species (ROS) production, coupled with downregulation of anti-apoptotic molecules (Bcl-2, Bcl-xL) led to reduction of mitochondrial membrane potential (MMP) and release of cytochrome c in both human breast cancer cells treated with vernodalin. Release of cytochrome c from mitochondria to cytosol triggered activation of caspase cascade, PARP cleavage, DNA damage and eventually cell death. Conclusions/Significance: To the best of our knowledge, this is the first comprehensive study on cytotoxic and apoptotic mechanism of vernodalin isolated from the Centratherum anthelminticum (L.) seeds in human breast cancer cells. Overall, our data suggest a potential therapeutic value of vernodalin to be further developed as new anti-cancer drug.